Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.2754/avb200776040613
|View full text |Cite
|
Sign up to set email alerts
|

Etoricoxib in the Prevention of Rat Mammary Carcinogenesis

Abstract: Orendáš P., I. Ahlers, P. Kubatka, E. Ahlersová, B. Bojková, M. Kassayová, L. Friedmanová, J. Kisková, I. Ďatelinka, M. Starostová: Etoricoxib in the Prevention of Rat Mammary Carcinogenesis. Acta Vet. Brno 2007, 76: 613-618. Several experimental studies suggest that non-steroidal antiinflammatory drugs have chemopreventive effects in mammary carcinogenesis. In this study, tumour suppressive effects of a selective inhibitor of cyclooxygenase-2 (COX-2) etoricoxib in the prevention of N-methyl-Nnitrosourea (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In our experiment, celecoxib markedly decreased tumor frequency per group and animal but increased tumor volume. Similar changes in tumor volume were found after etoricoxib application at a dose of 0.025mg/g diet [13]. As opposed to the effect of celecoxib and etoricoxib, administration of rofecoxib in the study by Kubatka et al [12] decreased tumor volume.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In our experiment, celecoxib markedly decreased tumor frequency per group and animal but increased tumor volume. Similar changes in tumor volume were found after etoricoxib application at a dose of 0.025mg/g diet [13]. As opposed to the effect of celecoxib and etoricoxib, administration of rofecoxib in the study by Kubatka et al [12] decreased tumor volume.…”
Section: Discussionmentioning
confidence: 52%
“…Dietary administered rofecoxib (selective COX-2 inhibitor) in NMUinduced mammary carcinogenesis in female Sprague-Dawley rats markedly decreased tumor incidence and frequency and prolonged latency period by 8 days [12]. The study focused on prevention of NMU-induced mammary carcinogenesis by etoricoxib (selective inhibitor COX-2) administered with diet to female Sprague-Dawley rats reported a tumor suppressive effect at a higher dose (0.025 mg/1 g diet) documented by a slight decrease in tumor incidence, tumor frequency per group, and prolonged latency by 7 days [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a tumor suppressive effect at a higher dose (0.025 mg g −1 diet) documented by a decrease in tumor incidence, tumor frequency per group and prolonged latency by 7.3% (Orendáš et al 2007). Abou-Issa et al (2001) reported inhibition in DMBA-induced mammary carcinogenesis in female Sprague-Dawley rats by celecoxib (0.25 g kg −1 , 0.50 g kg −1 , 1.00 g kg −1 or 1.50 g kg −1 diet) administered with diet.…”
Section: Discussionmentioning
confidence: 64%
“…Our group proved the chemopreventive effects of indomethacin administered in drinking water (Môci-ková-Kalická et al 2001), nimesulide applied subcutaneously (Kubatka et al 2002), rofecoxib (Kubatka et al 2003), etoricoxib (Orendáš et al 2007), and celecoxib (Orendáš et al 2009), all administered in the diet to female Sprague-Dawley rats with chemically-induced mammary tumors. Generally, at least 90% of mammary tumors showed malignant features, cribriform carcinoma in situ and invasive adenocarcinomas prevailed; the malignant/benign tumor ratio maintained regardless of oncostatic efficacy (Orendáš et al 2009).…”
Section: Introductionmentioning
confidence: 89%